Student ownership within instrumental ensembles - Kirby, Alexander (Kansas State University, 2020)
In this report, I will describe a lesson in which students learned how to take ownership within the ensemble by going through the process of creating and designing a marching band show. As directors, we know how much thought and time go into planning a marching show. My students will select a theme and three tunes that fit that theme through JW Pepper (a music publisher), vote for a show from a list compiled of their classmates' themes that were created, design props that could work for the show, and choose silks for the guard. While going through this process, students will design their show for the 2020 season and give them a closer connection to the show. Through my time at Kansas State University, I have developed as an educator in many ways. One of the most busy times during a band director’s life is the marching season and I kept returning to The Dynamic Marching Band: A Resource Book (2017). There is a chapter titled Director Band/ Life Balance (p. 479) and one of the first things it addresses is burnout and that is something that I was feeling at the end of the 2018-2019 school year. I wanted that to change, so I started by identifying my stress triggers: students forgetting materials, rehearsals not going the way I had imagined, and the amount of time away from my wife. All of those could be easily fixed by me through organization. I started having multiple copies of drill sheets and music parts available for students to get on their own at a designated location in the classroom as well as that uploaded to our google classroom that they could print out if they knew they had lost it before rehearsal. This allowed me to get in the mindset and focus on our rehearsal and not have to make copies right before. To help with the flow of rehearsals and making sure the ensemble was always moving in the right direction I started having meetings with my student leaders after our evening rehearsal to talk about what went well, what could have gone better, and where do we need to go from here. This really helped me understand what concepts my students were not grasping and helped to obtain more meaningful and productive rehearsals. The combination of finding solutions to my students not having their materials and being able to have more successful rehearsals fixed the time away from my wife problem on its own. Although this took more prep during the summer it made for an easier fall and made me happier, which in return made my students happier. During my time in Kansas State's Masters of Music program, I reflected on how to adjust my rehearsal techniques to keep my students engaged.. When students are able to stay engaged, they then start to take ownership within the program. Through this report, I will share my lesson which engaged the students and caused them to take ownership for the upcoming marching season.
Keywords: Music; Education; Instrumental; Ownership